The Transformation of the Islamic Broadcasting Communication Paradigm in the Multiplatform Journalism Ecosystem: A Phenomenological Study of the Virality of "Tepuk Sakinah" - Bayu Firmansyah; Ahmad Samsudin; Cecep Hidayattulloh (Advances In Social Humanities Research, 2026)
This research report presents a comprehensive analysis of the "Tepuk Sakinah" phenomenon, initiated by the Menteng Religious Affairs Office (KUA) and which became viral across various social media platforms between 2024 and 2025. Within the context of multiplatform journalism and evolving strategies in Islamic broadcasting communication, this phenomenon represents a fundamental shift in how state religious institutions engage with the digital public. This study employs a qualitative approach with an extensive literature review, integrating the STEPPS Framework for content virality, technological determinism, innovation diffusion theory, and cultural adaptation. The analysis highlights how content originating from Instagram Reels is transformed through TikTok's remix culture, amplified by online news portals, and ultimately triggers a national discourse on contemporary da'wah methods. The findings indicate that "Tepuk Sakinah" serves as an edutainment bridge, successfully breaking through rigid bureaucratic communication barriers and transforming passive audiences into active participants through User Generated Content (UGC). Nevertheless, this phenomenon has also sparked critical debates regarding the "infantilization of citizens" and the desacralization of marital values.